Travel guides, urban spatial imaginaries and LGBTQ+ activism: The case of Damron guides. (May 2021) - Knopp, Larry; Brown, Michael
In this paper we focus on LGBTQ+ travel guides and the creation of a North American LGBTQ+ urban imaginary as forms and facilitators of activism. Specifically, we consider one of the few continuously published sources detailing such an imaginary in the mid-20th century and its construction of an 'epistemological grid' onto which entries were placed. We briefly situate the guides in the context of an emerging (and frequently politicised) mid-20th-century LGBTQ+ media ecosystem, then proceed to a detailed analysis of the imaginary they evoke. Cities are the guides' assumed building-blocks, along with certain other ontologies, most notably bars, sex establishments and other meeting places (though these change over time). As aggregators of information at a national scale, the guides standardised and communicated particular notions of what LGBTQ+ space was (and is). At the same time, as way-finding tools they helped readers navigate actual communities at the local scale. In so doing, we argue, Damron guides helped shape early forms of LGBTQ+ identity and community in North America – including the establishment of 'gaybourhoods'. We therefore interpret the guides as both activist and facilitators of activism. They claimed space at an abstract level while simultaneously facilitating place-making, territorialisation and simple survival strategies by actual people on the ground. Our analysis contributes to understandings of the relationship, over time and at multiple scales, between travel guides, an urban-based North American spatial imaginary and LGBTQ+ activism. It also highlights Damron guides' potential as a rich source of data.